(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
Vocabulary learning is very necessary and an indispensable part of any language learning process. In the ESL context, vocabulary not only supports the four language skills; listening, speaking, reading, and writing, but also mediates between ESL students and content-area classes in that the students often find that lack of vocabulary knowledge is an obstacle to learning. This article focuses on and discusses effective strategies for teaching vocabulary to young learners which greatly assist English language learners in their journey of language acquisition and also expedite the language learning process. This study is aimed to describe the techniques used by the teacher in teaching English vocabulary for young learners. This study was conducted by using three techniques: observation and interview. The investigation revealed that the teacher applied various techniques in teaching vocabulary which divided into two stages. For presenting new words, using flashcards and miming are preferred by the teacher in this study. And the final in getting students to pra practice the words they have learnt, the teacher mostly employed identifying and matching task.